A separator for sodium metal secondary battery and a sodium metal secondary battery
Patent Information
- Application Number
- CN202611152197.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-20
AI Technical Summary
[0003]然而,该技术仍面临诸多挑战,其中最主要的问题是钠金属在沉积/剥离过程中巨大的体积膨胀与收缩
受限于钠金属二次电池的工作原理,充电时钠离子在负极侧形成钠金属,电池体积膨胀;放电时钠金属剥离为钠离子,电池体积收缩。为了解决上述问题,本申请创新性的提出一种钠金属二次电池用隔膜,该隔膜由基膜、陶瓷层、弹性涂层组成,可以有效缓解电池体积膨胀收缩效应,具体原理如下:
Abstract
Description
Technical Field
[0001] This application relates to a separator for sodium metal secondary batteries and a sodium metal secondary battery, belonging to the technical field of sodium metal secondary battery technology. Background Technology
[0002] Sodium metal secondary batteries benefit from the abundance of sodium in the Earth's crust, low raw material costs, and high theoretical specific capacity (1166 mAh g). -1 With its outstanding advantages such as excellent low-temperature performance, it has become a key candidate technology for the next generation of high-energy-density, low-cost energy storage and power batteries, and has irreplaceable application prospects in fields such as grid energy storage, rail transit, and portable power supplies.
[0003] However, this technology still faces many challenges, the most significant of which is the enormous volume expansion and contraction of sodium metal during deposition / stripping. Sodium metal has an extremely high theoretical volume change rate (up to several hundred percentage points), and the massive mechanical stress generated during repeated cycles leads to the following key defects: localized stress concentration induces dendrite growth, easily puncturing the diaphragm and causing internal short circuits and safety accidents; electrode structure collapses, and active material detaches from the current collector, resulting in rapid capacity decay and short cycle life; conventional polyolefin diaphragms (such as PE and PP) have low mechanical modulus and poor elastic recovery, making them prone to irreversible deformation, pore blockage, or rupture under long-term volume stress, failing to maintain stable ion transport channels and electrode-diaphragm interface contact.
[0004] Therefore, there is an urgent need to develop a new type of membrane material that can effectively buffer and adapt to the volume expansion of sodium metal, maintain interfacial mechanical stability and ion transport efficiency, in order to overcome the bottleneck of cycle stability and safety of anode-free sodium batteries.
[0005] Currently, the industry's solutions to address the severe problem of battery volume expansion and contraction mainly focus on separator coatings and other related issues.
[0006] For example, Chinese patent CN202022126414.2 relates to a lithium-ion battery separator and battery with an elastic coating. The battery separator includes: a first porous base film layer, an elastic coating, a second porous base film layer, a spherical silicone resin coating, a polymer elastic microsphere coating, and aluminum nitride particles. Because the elastic coating allows the separator to remain in close contact with the positive and negative electrodes during battery charging and discharging, it can greatly improve the battery's cycle performance and prevent relative displacement of the separator during charging and discharging. This solution can buffer the volume expansion of sodium metal, but the elastic microspheres used are made of polymer material, which will swell the electrolyte and reduce the battery's kinetic performance. Summary of the Invention
[0007] In view of the above problems, the first objective of this application is to provide a separator for sodium metal secondary batteries, which can be compressed as the battery expands and rebounds when the battery contracts, thus alleviating stress accumulation in the battery. Simultaneously, this separator can increase the sodium ion transport number without causing a loss of kinetic performance.
[0008] The technical solution adopted in this application is as follows: A separator for sodium metal secondary batteries includes a base membrane, on which a ceramic layer and an elastic coating are sequentially disposed at least on one side. The elastic coating includes elastic particles and a binder. The elastic particles have a core-shell structure, with an interior of MOF material capable of adsorbing anions and an exterior of polymer material.
[0009] Further settings are as follows: The base membrane is selected from one or more of polyethylene membrane, polypropylene membrane, polyethylene / polypropylene / polyethylene three-layer composite membrane, polyimide membrane, and polyvinylidene fluoride porous membrane; the thickness of the base membrane is 5-18 micrometers.
[0010] The ceramic layer is selected from one or more of alumina, boehmite, barium titanate, barium sulfate, and silicon dioxide; the thickness of the ceramic layer is 1-5 micrometers.
[0011] The thickness of the elastic coating is 5-20 micrometers, preferably 10 micrometers.
[0012] The mass of the elastic particles accounts for 95-99% of the total mass of the elastic coating, preferably 98%.
[0013] The D50 of the elastic particles is 0.5-2 micrometers, preferably 1 micrometer.
[0014] The MOF material is selected from one or more of ZIF-8, MOF-5, Zn-MOF-74, Mg-MOF-74, Mg-BTC, Ca-BDC, Ca-BTC, ZIF-7, ZIF-67, Zn-BTC, Mg-CUK-1, and Zn-Mg-MOF-74, with ZIF-8 being preferred. The D50 of the MOF material is 0.1-0.3 micrometers, preferably 0.2 micrometers.
[0015] Furthermore, considering the composite effect and elasticity of the polymer and MOF material, the polymer material is preferably polyurethane.
[0016] Specifically, the polyurethane is prepared by an addition polymerization reaction of diisocyanate and polyol to form urethane bonds (-NHCOO-). The diisocyanate can be one or more of IPDI (isophorone diisocyanate), HDI (hexamethylene diisocyanate), MDI (diphenylmethane diisocyanate), HMDI (hydrogenated MDI), and TDI (toluene diisocyanate), preferably IPDI. The polyol can be one or more of PPG (polypropylene glycol), PTMG / PTHF (polytetrahydrofuran glycol), PEG (polyethylene glycol), 1,4-butanediol, and 1,6-hexanediol, preferably PPG. The molar ratio of diisocyanate to polyol is 1:0.8 to 1.2, preferably 1:1. A catalyst is preferably added to the addition polymerization reaction to accelerate polymerization; in this application, DBTDL (dibutyltin dilaurate) is used as the catalyst.
[0017] The adhesive is selected from one or more of PVDF, SBR, CMC, and PAA.
[0018] The ceramic layer and the elastic coating can be disposed on one side of the base film or on both sides of the base film, that is, both sides of the base film are respectively provided with a ceramic layer and an elastic coating, wherein the elastic coating is disposed on the outermost side of the base film.
[0019] The base film can be one layer or more, the ceramic layer can be one layer or more, and the elastic coating can be one layer or more.
[0020] A second objective of this application is to provide a method for preparing the aforementioned diaphragm, comprising the following steps: (1) Add diisocyanate and polyol to DME in a certain proportion, heat to 60-80℃, and stir continuously to make it polymerize evenly to obtain polymer emulsion; (2) Add MOF material to polymer emulsion and stir until uniform. After drying, core-shell structured elastic particles can be obtained. In particular, by controlling the ratio of MOF material to polymer in polymer emulsion, elastic particles with different particle sizes can be obtained. (3) After the above elastic particles and binder are mixed evenly in proportion, they are coated on the surface of the base film to obtain the sodium metal secondary battery separator of this application.
[0021] The third objective of this application is to provide an application of the aforementioned separator in a sodium metal secondary battery.
[0022] The sodium metal secondary battery includes an anode electrode, a cathode electrode, an electrolyte, and a separator. The anode electrode, cathode electrode, and separator can be stacked or wound to form an electrode assembly.
[0023] The anode electrode is at least one of copper foil, aluminum foil, carbon-coated copper foil, carbon-coated aluminum foil, porous copper foil, and porous aluminum foil.
[0024] The cathode electrode comprises an active material, conductive carbon, a binder, and a current collector.
[0025] The active substance is one or more of sodium ferric pyrophosphate, sodium ferric sulfate, sodium vanadium phosphate, sodium vanadium fluorophosphate, layered oxides, Prussian blue, Prussian white and their analogues.
[0026] The conductive carbon is one or more of Superp, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, and graphene.
[0027] The adhesive is one or more of styrene-butadiene rubber, acrylonitrile, acrylate, polyvinylidene fluoride (PVDF), polytetrafluoroethylene, and carboxymethyl cellulose.
[0028] The current collector is one or more of aluminum foil, carbon-coated aluminum foil, and porous aluminum foil.
[0029] The electrolyte includes sodium salts and ether solvents.
[0030] The sodium salt is sodium hexafluorophosphate with a concentration of 0.8-5 mol / L. In some embodiments, some auxiliary salts may be added to optimize battery performance, including one or more of sodium tetrafluoroborate, sodium trifluoromethanesulfonate, sodium bis(oxalate)borate, sodium difluorooxalateborate, sodium difluorobis(oxalate)phosphate, sodium tetrafluorooxalate phosphate, sodium bis(trifluoromethanesulfonate)imide, sodium di(fluorosulfonyl)imide, and sodium perchlorate, with an auxiliary salt concentration of 0.1-0.5 mol / L.
[0031] The ether solvent is one or more of the following: ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, tetrahydrofuran, 3-methyltetrahydrofuran, 1,3-dioxopentane, tetrahydropyran, 1,3-dioxane, and 1,4-dioxane.
[0032] The beneficial effects of this application are as follows: Due to the limitations of the working principle of sodium metal secondary batteries, sodium ions form sodium metal on the negative electrode side during charging, causing the battery volume to expand; during discharging, sodium metal is stripped away into sodium ions, causing the battery volume to shrink. To address these issues, this application innovatively proposes a separator for sodium metal secondary batteries. This separator consists of a base film, a ceramic layer, and an elastic coating, which can effectively mitigate the battery volume expansion and contraction effects. The specific principle is as follows: (1) An elastic coating is applied to the separator, consisting of micron-sized elastic microspheres with a core-shell structure. The microspheres are made of MOF material inside and a polymer outside. Thanks to the core-shell structure design, the microspheres have excellent elasticity, can be compressed and deformed under pressure, and can rebound when the stress decreases. At the same time, the MOF material gives the microspheres a certain rigidity, so they will not be crushed even when fully charged. Therefore, the elastic microspheres have a long lifespan and can be adapted to the entire life cycle of sodium metal secondary batteries.
[0033] (2) This application effectively solves the problem that the polymer on the diaphragm will swell the electrolyte in the prior art.
[0034] In existing sodium metal secondary battery systems, the polymer on the separator swells in the electrolyte, forming localized gel electrolytes, which slows down the migration rate of sodium ions and affects the battery's kinetic performance. The separator prepared in this application has MOF material inside its elastic microspheres, which contains positively charged cations that can anchor anions in the electrolyte, increasing the sodium ion transference number. Therefore, the separator design provided in this application does not cause a loss of kinetic performance.
[0035] The present application will be further described below with reference to specific embodiments. Detailed Implementation
[0036] The present application will be further described below with reference to specific embodiments. Unless otherwise specified, the raw materials and reagents described in the embodiments are all existing technologies in the field or commercially available products.
[0037] Example 1
[0038] This embodiment mainly realizes the preparation of a separator for sodium metal secondary batteries.
[0039] (1) Preparation of elastic particles: IPDI and PPG were added to DME in a 1:1 mass ratio, heated to 70°C, and continuously stirred to polymerize uniformly, thus obtaining a polymer emulsion. ZIF-8 with a D50 of 200 nm was added to the polymer emulsion and stirred until uniform. The mass ratio of ZIF-8 added was 30% of the total mass of IPDI and PPG. After drying, elastic particles with a D50 of 1 micrometer were obtained.
[0040] (2) Preparation of the diaphragm: A 7-micron thick polyethylene porous membrane with 1-micron thick alumina ceramic layers on both sides was selected. The above elastic particles and PVDF were added to water at a mass ratio of 98:2. After mixing evenly, the mixture was coated onto the membrane surface on one side with a coating thickness of 10 microns. After drying, it was cut into rectangles with dimensions of 60 mm * 47 mm for later use.
[0041] Example 2-Example 3 The preparation method is the same as in Example 1, except that the type of MOF material added is adjusted as shown in Table 1.
[0042] Examples 4-5 The preparation method is the same as in Example 1, except that the particle size of the added MOF material is adjusted as shown in Table 1.
[0043] Examples 6-7 The preparation method is the same as in Example 1, except that the type of diisocyanate added is adjusted as shown in Table 1.
[0044] Examples 8-9 The preparation method is the same as in Example 1, except that the types of polyols added are adjusted as shown in Table 1.
[0045] Examples 10-11 The preparation method is the same as in Example 1, except that the molar ratio of diisocyanate and polyol is adjusted as shown in Table 1.
[0046] Examples 12-13 The preparation method is the same as in Example 1, except that elastic particles of different sizes can be obtained by controlling the mass ratio of ZIF-8. See Table 1 for details. By adjusting the ZIF-8 addition ratio to 50% of the total mass of IPDI and PPG, elastic particles with a particle size D50 of 0.5 micrometers were obtained.
[0047] By adjusting the ZIF-8 addition ratio to 15% of the total mass of IPDI and PPG, elastic particles with a particle size D50 of 2 micrometers were obtained.
[0048] Examples 14-15 The preparation method is the same as in Example 1, except that the mass ratio of elastic particles in the elastic coating is adjusted as shown in Table 1.
[0049] Examples 16-17 The preparation method is the same as in Example 1, except that the thickness of the elastic coating is adjusted as shown in Table 1.
[0050] Comparative Example 1 A porous polyethylene membrane with a base film thickness of 7 micrometers was used, with a 1-micrometer-thick alumina ceramic layer on both sides, but no elastic coating was applied.
[0051] Comparative Example 2 The preparation method is the same as in Example 1, except that the elastic particles prepared contain only MOF material ZIF-8 and no polymer material is added.
[0052] Comparative Example 3 The preparation method is the same as in Example 1, except that the elastic particles prepared contain only polymer materials and no MOF material, namely ZIF-8, is added.
[0053] Application Examples
[0054] The membranes prepared in the aforementioned examples and comparative examples were applied to sodium metal secondary batteries, and their performance was tested.
[0055] Sodium metal secondary batteries consist of a cathode, an anode, a separator, and an electrolyte.
[0056] Cathode electrode: Active material sodium iron pyrophosphate, conductive agent Super P, and binder PVDF are mixed at a mass ratio of 98:1:1. N-methylpyrrolidone solvent is added and stirred until homogeneous, resulting in a cathode slurry with a viscosity of 40,000 mPas and a solid content of 65%. The cathode slurry is then coated on one side using a coating machine at a rate of 18 mg / cm². 2 The loading is coated on both sides of the aluminum foil, dried thoroughly until the moisture content is below 150 ppm, and then cut into rectangles of 56 mm × 43 mm as positive electrode sheets.
[0057] Anode electrode: Select carbon-coated aluminum foil with a thickness of 13 micrometers and cut it into rectangles with a size of 58 mm * 45 mm for later use.
[0058] Electrolyte: In an argon atmosphere glove box, the water and oxygen contents are both less than 0.1 ppm. Ethylene glycol dimethyl ether is used as a solvent, and a certain amount of sodium hexafluorophosphate is dissolved in the solvent to obtain a uniform, colorless, and transparent electrolyte with a sodium hexafluorophosphate concentration of 1 mol / L.
[0059] Battery assembly: The cathode electrode, separator, and anode electrode are stacked in sequence, with 10 layers of cathode electrode and 11 layers of anode electrode to obtain a bare cell. The bare cell is then welded with tabs and placed in an aluminum-plastic film outer packaging bag to obtain a dry cell. Electrolyte is injected into the dry cell and vacuum hot-pressed for sealing. After standing at room temperature for 10 hours, hot and cold pressing, formation, shaping, and capacity testing are carried out in sequence to obtain a sodium metal secondary battery with a rated capacity of 800mAh.
[0060] Performance testing: Cycle performance test: The ambient temperature was set to 25℃. The prepared battery was left to stand for 1 hour, then charged at a constant current of 0.5C to 3.35V, followed by constant voltage charging at 3.35V until the current dropped to 0.05C. After standing for 1 hour, it was discharged at a constant current of 1C to 2V to obtain the discharge capacity. The above steps were repeated for the same battery, and the number of cycles when the discharge capacity decayed to 80% was recorded. The number of cycles completed at this point is taken as the battery cycle life.
[0061] Expansion ratio test: Use a micrometer to measure the thickness of the cell at five locations and take the average value as the cell thickness. First, measure the thickness of the battery before charging, and then measure the thickness of the battery after it is fully charged to 3.35V with a constant current of 0.5C. Divide the fully charged thickness by the thickness before charging to get the expansion ratio.
[0062] The test results are shown in Table 1.
[0063] Table 1 .
[0064] Refer to Table 1: As can be seen from Examples 1-3, 6-9 and Comparative Example 1, the elastic particles prepared by this application, which contain different types of MOF materials, diisocyanates and polyols, can all alleviate battery swelling, protect the battery structure, and thus improve battery cycle life.
[0065] As can be seen from Examples 1 and 4-5, the particle size of the MOF material in the elastic particles provided in this application has a significant impact on the performance. If the particle size is too large, the elastic particles will not be elastic enough; if the particle size is too small, they will not be able to fully anchor the anions in the electrolyte, resulting in battery polarization.
[0066] As can be seen from Examples 1 and 10-11, the molar ratio of diisocyanate to polyol in the elastic particles provided in this application has a significant impact on performance. Too high or too low a ratio will lead to insufficient polymer addition polymerization and result in monomer residue.
[0067] As can be seen from Examples 1 and 12-13, the particle size of the elastic particles provided in this application has a significant impact on the performance. If the particle size is too large, the proportion of MOF material is insufficient, which affects the kinetics and polarization. If the particle size is too small, the proportion of polymer is insufficient, and the elasticity decreases.
[0068] As can be seen from Examples 1 and 14-15, the mass ratio of elastic particles in the elastic coating provided in this application has a significant impact on performance. If the mass ratio of elastic particles is too large, the adhesion will be insufficient and the elastic particles will easily fall off. If the mass ratio is too small, the compressible space of the elastic coating will decrease.
[0069] As can be seen from Examples 1 and 16-17, the thickness of the elastic coating provided in this application has a significant impact on performance. If the thickness is too large, the battery polarization is large; if the thickness is too small, the compressible space of the elastic coating decreases.
[0070] As can be seen from Example 1 and Comparative Examples 1-3, the MOF material and polymer material in the elastic particles provided in this application have a significant synergistic effect. When only MOF material is used, the coating is not elastic, while when only polymer material is used, the battery polarization is large, resulting in capacity decay.
[0071] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A separator for sodium metal secondary batteries, characterized in that: The material includes a base film, on which a ceramic layer and an elastic coating are sequentially disposed on at least one side. The elastic coating includes elastic particles and a binder. The elastic particles have a core-shell structure, with an interior of MOF material capable of adsorbing anions and an exterior of polymer material.
2. The separator for a sodium metal secondary battery according to claim 1, characterized in that: The base membrane is selected from one or more of polyethylene membrane, polypropylene membrane, polyethylene / polypropylene / polyethylene three-layer composite membrane, polyimide membrane, and polyvinylidene fluoride porous membrane; the thickness of the base membrane is 5-18 micrometers.
3. The separator for a sodium metal secondary battery according to claim 1, characterized in that: The ceramic layer is selected from one or more of alumina, boehmite, barium titanate, barium sulfate, and silicon dioxide; the thickness of the ceramic layer is 1-5 micrometers.
4. The separator for a sodium metal secondary battery according to claim 1, characterized in that: The thickness of the elastic coating is 5-20 micrometers.
5. The separator for a sodium metal secondary battery according to claim 1, characterized in that: The elastic particles have a D50 of 0.5-2 micrometers, and their mass accounts for 95-99% of the total mass of the elastic coating.
6. The separator for a sodium metal secondary battery according to claim 1, characterized in that: The MOF material is selected from one or more of ZIF-8, MOF-5, Zn-MOF-74, Mg-MOF-74, Mg-BTC, Ca-BDC, Ca-BTC, ZIF-7, ZIF-67, Zn-BTC, Mg-CUK-1, and Zn-Mg-MOF-74, and the D50 of the MOF material is 0.1-0.3 micrometers.
7. The separator for a sodium metal secondary battery according to claim 1, characterized in that: The polymer material is polyurethane.
8. The separator for a sodium metal secondary battery according to claim 1, characterized in that: The adhesive is selected from one or more of PVDF, SBR, CMC, and PAA.
9. A method for preparing a separator for a sodium metal secondary battery as described in claim 1, characterized in that: Includes the following steps: (1) Add diisocyanate and polyol to DME in a certain proportion, heat to 60-80℃, and stir continuously to make it polymerize evenly to obtain polymer emulsion; (2) Add MOF material to polymer emulsion and stir until uniform. After drying, core-shell structured elastic particles can be obtained. (3) After the elastic particles and binder are mixed evenly in proportion, they are coated on the surface of the base film to obtain the separator for sodium metal secondary batteries.
10. The application of the separator for sodium metal secondary batteries according to claim 1 in sodium metal secondary batteries.
Citation Information
Patent Citations
Lithium ion battery diaphragm containing elastic coating and battery
CN213184504U